As thick as three in a bed. Issue 14 (14th July 2016) - Scheidegger, Christoph
Abstract : During the evolution of the lichen symbiosis, shifts from one main type of photobiont to another were infrequent (Miadlikowska et al .2006 ) but some remarkable transitions from green algal to diazotrophic cyanobacterial photobionts are known from unrelated fungal clades within the ascomycetes. Cyanobacterial, including tripartite, associations (green algal and cyanobacterial photobionts in one lichen individual) facilitate these holobionts to live as C‐ and N‐autotrophs. Tripartite lichens are among the most productive lichens, which provide N‐fertilization to forest ecosystems under oceanic climates (Peltigerales) or deliver low, but ecologically significant N‐input into subarctic and alpine soil communities (Lecanorales, Agyriales). In this issue of Molecular Ecology, Schneider et al . (2016) mapped morphometric data against an eight‐locus fungal phylogeny across a transition of photobiont interactions from green algal to a tripartite association and used a phylogenetic comparative framework to explore the role of nitrogen‐fixing cyanobacteria in size differences in the Trapelia–Placopsis clade (Agyriales). Within the group of tripartite species, the volume of cyanobacteria‐containing structures (cephalodia) correlates with thallus thickness in both phylogenetic generalized least squares and phylogenetic generalized linear mixed‐effects analyses, and the fruiting body core volume increased ninefold. The authors conclude that cyanobacterial symbiosis appears to have enabled lichens to overcome size constraints in oligotrophic environments such as rock surfaces. The Trapelia–Placopsis clade analyzed by Schneider et al . (2016) is an exciting example of interactions between ecology, phylogeny and lichen biology including development – from thin crustose green algal microlichens to thick placodioid, tripartite macrolichens: as thick as three in a bed (Scott1820 ).